1998
DOI: 10.1159/000045016
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease following Polycythemia vera: In vitro and in vivo Response of Erythroid Progenitors to Erythropoietin and Effects of Sera on Normal Erythropoiesis

Abstract: We investigated the in vitro erythroid progenitor growth and the effects of sera on normal-marrow CFU-E (colony-forming units – erythroid) growth in 2 patients with renal failure on regular hemodialysis following a prior history of polycythemia vera (PV). PV was diagnosed 3 and 11 years, respectively, before the development of terminal renal failure. One of the patients had entered a spent phase of PV as characterized by diffuse extensive myelofibrosis and anemia; the other also had mild myelofibrosis. The ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…[2,3]. On the other hand, it was also reported that exogenous EPO administration enhanced the erythropoiesis in this condition [1,4,5]. The data from our patient show that the hemoglobin values in PV concurrent with chronic renal failure are affected by lack of EPO.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…[2,3]. On the other hand, it was also reported that exogenous EPO administration enhanced the erythropoiesis in this condition [1,4,5]. The data from our patient show that the hemoglobin values in PV concurrent with chronic renal failure are affected by lack of EPO.…”
supporting
confidence: 55%
“…Dear Sir, Recently, it was reported that there were 9 polycythemia vera (PV) cases associated with end-stage renal disease (ESRD) [1]. Of them, 2 had PV and ESRD at the time of diagnosis, 3 were on regular dialysis treatment before the diagnosis of PV, and 4 developed ESRD after PV diagnosis.…”
mentioning
confidence: 99%
“…Under these conditions, uremic patients under artificial hemodialysis with medical administration of an EPO agent showed a markedly high serum EPO level of >1,000 mU/ml, independent of the cause of death and survival time, indicating interference due to medical intervention before death. Such findings may be seen for patients within about 12 h after intravenous injection of an EPO agent when the elimination rate is considered [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Data from animal models have shown that reduction in nephron mass exposes the remaining nephrons to adaptive hemodynamic changes that are intended to sustain renal function acutely but may be detrimental for longer time periods (35). Other reports suggest that excessive erythrocytosis plays a role in the development of chronic renal failure in patients with preexisting polycythemia vera (40,41). On the other hand, patients with chronic mountain sickness at high altitude showed reduced kidney plasma flow and increased filtration fraction as hematocrit rose (22,25).…”
Section: Discussionmentioning
confidence: 99%